« Durabilité des bétons autoplaçants à base de VASE ET DE pouzzolane» - BELARIBI Omar (My University, 2015)
Because of the specificities of self-compacting concrete (SCC), especially regarding their high volume paste content and the presence of large amounts of mineral admixtures and substitutes, the behavior in fresh and hardened state and the durability of these concretes are strongly influenced by these two parameters. Some treated sediments acquire pozzolanic properties and can be used as additions or substitutes to the cement. This possibility makes of concrete technology a privileged way of enhancement. The present study aims to contribute to the enhancement of the treated mud of Chorfa and Fergoug dam (situated in west of Algeria) as a mineral partial substitute for CPA CEMI 42.5 cement in the composition of an economic and preferment mortars and self-compacting concretes. The aim is to compare the influence of the incorporation of this calcined mud to the natural pozzolana of Beni Saf (situated, also in west of Algeria) in (SCC) on their physical, mechanical behavior and their durability of these concretes in short, medium and long term. The study was conducted on four SCCs, the first based on 20% natural pozzolana Beni Saf (SCC-PZ), the second based on 20% of the calcined mud of Fergoug dam (SCC-VF) and of Chorfa dam (SCC-VC) and a control SCC without additions to the need for comparison . Apart from the economic interest of the SCCs based on calcined mud, our study showed that these concretes have comparable performances to that obtained on SCC based on natural pozzolana (SCC-PZ). In fact, concerning compressive strengths, our study indicate that the SCC with calcined mud ((SCC-VC) and (SCC-VF)) present the best results especially at long term The results of the different following tests: the acid attack (HCl and H2SO4), carbonation and sulphate attack (Na2SO4 and MgSO4) show that the calcined mud has an influence roughly better than the natural pozzolana on the physic - mechanical behavior and durability of the SCC which it is incorporated.
Keywords: Dam of Chorfa – Dam of Fergoug – Calcined mud – Pozzolana – SCC containing mud - SCC containing pozzolana – Mechanical strength –Durability.